An advanced construction strategy of all-solid-state lithium batteries with excellent interfacial compatibility and ultralong cycle life. Issue 32 (1st August 2017) - Zhang, Zhihua; Zhao, Yanran; Chen, Shaojie; Xie, Dongjiu; Yao, Xiayin; Cui, Ping; Xu, Xiaoxiong
Abstract : The inferior cycle performance of All-solid-state lithium batteries (ASSLBs) resulting from the low mixed ionic and electronic conductivity in the electrodes, as well as the large interfacial resistance between the electrodes and the electrolyte have been optimized in this work. Abstract : The inferior cycle performance of All-solid-state lithium batteries (ASSLBs) resulting from the low mixed ionic and electronic conductivity in the electrodes, as well as the large interfacial resistance between the electrodes and the electrolyte need to be overcome urgently for commercial applications. Here, an advanced cell construction strategy has been proposed, in which a cohesive and highly conductive poly(oxyethylene) (PEO)-based electrolyte is employed both in the cathode layer and in the interface of the electrolyte/anode, leading to an ASSLB with superior interfacial contact between the electrolyte and the electrodes, and forming a three-dimensional ionic conductive network in the cathode layer. Especially, the NASICON-type ionic conductor covered with the PEO-based polymer, integrating the advantages of an inorganic electrolyte and organic electrolyte, presents an enhanced electrochemical stability and an excellent compatibility with the Li electrode. Consequently, the ASSLBs of LiFePO4 (LFP)/Li with this advanced construction strategy exhibit excellent interfacial compatibility, ultralong cycle life and high capacity, i.e., a reversible discharge capacity maintained at 127.8 mA h g −1 for the 1000 th cycle at 1C with a retention of 96.6%, and an initial discharge capacity of 153.4 mA h g −1 with a high retention of 99.9% after 200 cycles at 0.1C. Besides, the high-voltage monopolar stacked batteries with a bipolar structure can be fabricated conveniently, showing an open circuit voltage (OCV) of 6.63 V with a good cycle performance. In particular, the ASSLBs present outstanding safety in terms of nail penetration and burning in fire. Therefore, this advanced cell construction strategy may generate tremendous opportunities in the search for novel emerging solid-state lithium metal batteries.